Human Opportunities in the Kyrgyz Republic - Tiwari, Sailesh (World Bank, Washington, DC, 2017)
The Kyrgyz Republic has made some progress in improving its poverty and social indicators but the gains have been fragile and significant disparities remain within the country. The slowdown in economic growth in 2009 and the resulting uptick in poverty underscored the susceptibility of the economy to external shocks. In this report, author's tackle the issue of inequality in the Kyrgyz Republic by framing it along the notion of equity as opposed to equality. The reason for doing so is that it is easier to galvanize social consensus and policy action when the overarching principle guiding policy is fairness in the allocation and access to opportunities as opposed to equality of outcomes. A girl born in a remote village in the oblast of Naryn to a single, uneducated mother with four other siblings ought to have the same shot at becoming a doctor or an engineer as a boy with one sibling, born in an educated, two-parent household in Bishkek. Basic opportunities are defined as subset of goods and services for children, such as access to education, safe water on site, or reliable electricity that are critical in determining opportunities for economic advancement in life. These are either already affordable by society at large or could be in the near future, given the available technology. Opportunities among children are measured in this report by the Human Opportunity Index (HOI), which is the coverage rate of a particular basic service adjusted by how equitably the service is distributed among groups differentiated by circumstances. In discounting inequitable access, the HOI reflects how personal circumstances- for which the children cannot be held accountable-affect their basic opportunities. The key finding of this report is that the goal of equal opportunity remains distant in the Kyrgyz Republic: a child's circumstances such as her parents' socioeconomic status, region of residence, whether it is urban and rural etc. have a substantial bearing on the extent to which certain services are available to her. Similarly, opportunities pertaining to a healthy start in life adequate access to household infrastructure and amenities that ensure a stable, safe and stimulating childhood also have strong regional dimensions with entire regions being underserved. Finally, what this report has done is taken a snapshot of the distribution of opportunities in the Kyrgyz Republic for a particular year.